2015
DOI: 10.1007/s11664-015-3849-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited ZnS Precursor Layer with Improved Electrooptical Properties for Efficient Cu2ZnSnS4 Thin-Film Solar Cells

Abstract: Zinc sulfide (ZnS) thin films were prepared on indium tin oxide-coated glass by electrodeposition using aqueous zinc sulfate, thiourea, and ammonia solutions at 80°C. The effects of sulfurization at temperatures of 350°C, 400°C, 450°C, and 500°C on the morphological, structural, optical, and electrical properties of the ZnS thin films were investigated. X-ray diffraction analysis showed that the ZnS thin films exhibited cubic zincblende structure with preferred (111) orientation. The film crystallization impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…And also revealed the value of resistivity is lower than carrier mobility which caused to increase the conductivity by reducing the recombination rate by allowing more charge carriers to diffuse to adjacent layer. It is reported the resistivity range of ZnS varied from 102 Ω.cm to 106 Ω.cm [11] .From this work and previous literature shown in Table 2 it is concluded that there is direct relationship between carrier concentration and resistivity which proves these both are in directly proportional to each other. It is concluded the increase in concentration will be able to excite maximum charge carriers from bulk, hence mobility of charge carriers will be increased.…”
Section: Results and Analysissupporting
confidence: 68%
“…And also revealed the value of resistivity is lower than carrier mobility which caused to increase the conductivity by reducing the recombination rate by allowing more charge carriers to diffuse to adjacent layer. It is reported the resistivity range of ZnS varied from 102 Ω.cm to 106 Ω.cm [11] .From this work and previous literature shown in Table 2 it is concluded that there is direct relationship between carrier concentration and resistivity which proves these both are in directly proportional to each other. It is concluded the increase in concentration will be able to excite maximum charge carriers from bulk, hence mobility of charge carriers will be increased.…”
Section: Results and Analysissupporting
confidence: 68%
“…ZnS is an inexpensive semiconductor with an energy band gap of 3.72 eV in the cubic phase and 3.77 eV in the hexagonal wurtzite phase. In thin film photovoltaic devices, ZnS has been majorly employed as an n-type material to form a p-n junction by pairing with a p-type material, for example, Cu(In,Ga)Se 2 (CIGSe) [80] or Cu 2 ZnSnS 4 (CZTS) [81,82]. ZnS can be electrochemically deposited with either an alkaline electrolyte or an acidic electrolyte.…”
Section: Znsmentioning
confidence: 99%
“…ZnS can be electrochemically deposited with either an alkaline electrolyte or an acidic electrolyte. Mkawi et al reported the use of an aqueous electrolyte containing zinc sulfate (ZnSO 4 ), thiourea (CS(NH 2 ) 2 ) and ammonia (NH 3 ) for the deposition of ZnS on ITO-coated glass substrate [82]. The pH value of the electrolyte was 10 and the deposition was carried out at 80 • C. It was explained that NH 3 functioning as a complexing agent formed a complex with Zn and thus played a role in controlling the concentration of Zn 2+ through the common ion effect.…”
Section: Znsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistivity seems to vary between 18.4 to 0.63 Ωcm when the precursor for the copper atom is changed. Mkawi reported a lower resistivity value of 6.98 Ωcm for a copper concentration of 0.4 M [59]. The resistivity value is found to depend on carrier concentration and mobility.…”
Section: Electrical Analysismentioning
confidence: 89%